Digital microscopy (Amsterdam, Netherlands Elsevier/Academic Press, 2003)
This updated second edition of the popular methods book "Video Microscopy" shows how to track dynamic changes in the structure or architecture of living cells and in reconstituted preparations using video and digital imaging microscopy. Contains 10 new chapters addressing developments over the last several years. Basic information, principles, applications, and equipment are covered in the first half of the volume and more specialized video microscopy techniques are covered in the second half.--Provided by publisher.
Second edition of video microscopy
Includes bibliographical references and index.
Keywords: Microscopy; Image processing -- Digital techniques; Electronic books